Estimating the limit possibilities of the step charging system for capacitive energy storage - Batygin, Yu.V.; Chaplygin, E.A.; Sabokar, O.S. (Електротехніка і електромеханіка, 2016)
The aim of the article is to estimate the limit possibilities of step-by-step charging the capacitive energy storage which are caused
by the achievement of a balance among the processes of the receiving and losing of electromagnetic energy. Originality. For the
first time a step the charging system as a high power converter for pulsed load was considered, that allow to simplify similar
charging systems and make its chipper while saving output characteristics and common quality. Methodology of the analysis applied is based on the classic electric circuits theory. All of the resulted carried out, were obtained as the differential equation solutions and its behavior was analyses analytically. Results. The basic diagram of the step-by-step charging system what is an alternative to the traditional variant with the step-up transformer was described. This system realizes the serial charge voltage increasing by the separate portions of energy, which has been, accumulated preliminary in the inductive energy storage. The formulas
for estimating the limit possibilities of the step-by-step charging were got. These limits are caused by achieving a balance of the
entering and losing electromagnetic energy. The applicability of the formulas was illustrated by numerical examples. Practical
value. According to the results that were obtained, it is possible to note, that the step charging system is acceptable to be used as a
high power converter for capacitive storage charging. Описана принципиальная схема ступенчатого заряда емкости, альтернативной традиционному варианту с повышающим трансформатором и предполагающей последовательное повышение зарядного напряжения за счёт подачи
отдельных порций энергии, предварительно запасённой в обмотке специального индуктивного накопителя. Получены
формулы для оценки предельных возможностей ступенчатого заряда, обусловленных достижением баланса в процессах поступления и потерь электромагнитной энергии. Применимость формул проиллюстрирована численными примерами